PENGARUH INTENSITAS MENGIKUTI PENGAJIAN TERHADAP PSYCHOLOGICAL WELL-BEING (Studi Pada Jamaah Wanita Salafi di Kota Padang) - Hamidah, Radhyatul; Ardias, Widia Sri; ., Hasnawati (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2020)
The problem that recsearchers see is from the theory of Psychological well-being (PWB) which is defined as the condition of an individual where he has gained welfare for himself. One of the factors that influence PWB is religiosity, where religiosity can be calculated by the presence of a religious institution and the application of that religiosity value in daily activities. One of them is recitation, and regular recitation will bring peace by remembering Allah. This study aims to determine the effect of the intensity of following the recitation on psychological well-being among female congregations of routine salafi studies in Padang. The research method used is a quantitative method with a correlation research specification. The population in this study were 163 female worshipers. The research sample consisted of 78 worshipers. The sampling technique in this study uses a non-probability sampling technique, namely the voluntary sampling technique.The results of this study found that the female congregation of the routine salafi study in Padang was 23.4% of the effect of the intensity of following the recitation on psychological well-being in the female congregation of the routine salafi study in Padang. So that the intensity of following the recitation which was causing the psychological well-being of the female congregation was also moderate.